Using data envelopment analysis to support best-value contractor selection - Yang, Jyh-Bin; Wang, Han-Hsiang; Wang, Wei-Chih; Ma, Shin-Min (Journal of Civil Engineering and Management, 2016)
Selecting an appropriate contractor or supplier is essential to the successful implementation of a public procurement project. The Taiwan government frequently applies the best-value (BV) tendering method, a multi-criteria evaluation method, to procure projects. However, the selection process of the winner for a BV-based procurement project is generally subjective and thus is easily accused of corruptions. To develop a systematic method to support contractor selection, this study proposes using the Data Envelopment Analysis (DEA) to facilitate the criteria evaluations for each bidder during the short-listing stage. The evaluation results of using the DEA are a list of potential BV winners who are then suggested to enter into the final selection stage. Based on three case studies related to service procurement projects, this research finds that the DEA is suitable of assessing the relative efficiencies among bidders when the BV approach is applied. Lessons learned here should be helpful in applying the DEA to aid bid evaluations in other supplier selection problems.First published online: 24 Aug 2015